281 Effects of feeding endophyte-infected tall fescue seed to Angus steers on ergovaline concentration, lipid oxidation, and skeletal metmyoglobin reductase activity. (5th December 2019) - McClenton, Brandon; Goodman, Jack; Dong, Oanh; Sukumaran, Anuraj; Holtcamp, Alexander; Hart, Caitlin; Lemley, Caleb O; Aiken, Glenn; Schilling, Wes; Baldwin, Brian; Martin, Steven; Blanton, John; et al.
Abstract: This study was aimed to determine the ergovaline concentration, lipid oxidation, and skeletal metmyoglobin reductase activity in Angus steers fed with endophyte-infected tall fescue seed. Animals were blocked into light (n = 4, 205.5 ± 7.4 kg), medium (n = 5, 231.3 ± 8.2 kg), and heavy (n = 3, 272.7 ± 8.4 kg) groups and randomly assigned to either a KY31 seed treatment (6796 ppb ergovaline; 20 µg/kg BW; E+; n = 6) or a KY32 control (< 100 ppb; E-; n = 6) by Calan ® gates during a 70-d feeding period from June to August of 2015 (period 1), followed by a 150-d resting period and another 64-d feeding period from January to March of 2016 (period 2). In both periods, there was a 2-way treatment × time interaction for ergovaline concentration in blood (P = 0.002 and 0.022, respectively), with E+ steers having 0.59 to 0.95 nM more than E- steers on d 3 (P < 0.001). In period 1, TBARS values were greater in blood serum of E+ steers than in that of E- steers (6.56 vs. 2.56 µM MDA; P = 0.048) and an overall increase in MDA from d 0 (2.39 µM) to d 3 (7.59 µM) was also observed (P = 0.049). At slaughter, E+ steers had a blood TBARS value of 2.27 µM, greater than 1.15 µM in E- steers (P = 0.013). In postmortem muscle, the TBARS value was 0.68 and 0.77 µg/kg for E- and E+ steers, respectively (P = 0.239). There was no effect of endophyte-infected tall fescue seed on metmyoglobin reductase in longissimus thoracis (4.82 µM/min/g in E- muscle vs. 3.93 µM/min/g in E+ muscle; P = 0.484). Therefore, feeding endophyte-infected tall fescue seed increased ergovaline concentration and oxidative stress in the blood of Angus steers.